COGNITIVE INVESTIGATION OF THE INTEGRATED MENTAL BASIS OF CREATIVE WRITING - Maslova, Zhanna; Minakhin, Denis (European Scientific Journal, ESJ, 2014)
In the article it is suggested the cognitive theory of the poetic picture of the world as a methodological frame for further investigation of the poetic text. The main idea of the paper is that poetry as an art is based on the whole system of special conceptual structures which are the part of the conceptual picture of the world and these conceptual structures get representation in the language of the poetic text. The cognitive theory of the poetic picture of the world includes: defining the main cognitive function of the poetic picture of the world; defining the kind of knowledge, which is conceptualized through this function; structuring the field of this knowledge, highlighting its main structural elements which are under the process of conceptualization; defining the specific categories and categorical levels of the poetic picture of the world. Structural organization of the poetic picture of the world is the key point in the paper. It is stated that poetry as a kind of human cognitive activity reflects the experience of interaction between the human being and the world (“I”-system, “World”-system). the poetic picture of the world as a mental construct fixes standards, expectations and stereotypes about what events and situations may be the subject of poetry and what language form they should be represented in.